2017
DOI: 10.3168/jds.2016-11910
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis and pathways enrichment for lactation persistency in Canadian Holstein cattle

Abstract: Lactation persistency (LP), defined as the rate of declining milk yield after milk peak, is an economically important trait for dairy cattle. Improving LP is considered a good alternative method for increasing overall milk production because it does not cause the negative energy balance and other health issues that cows experience during peak milk production. However, little is known about the biology of LP. A genome-wide association study (GWAS) and pathway enrichment were used to explore the genetic mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 90 publications
3
54
0
1
Order By: Relevance
“…The second most significant association signal was at BTA20:29996719 (rs43116343), which is close to MRPS30 . A recent study showed MRPS30 to be associated with lactation persistence in Canadian Holstein cattle [ 19 ]. This lead SNP is also close to the growth hormone receptor, GHR [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The second most significant association signal was at BTA20:29996719 (rs43116343), which is close to MRPS30 . A recent study showed MRPS30 to be associated with lactation persistence in Canadian Holstein cattle [ 19 ]. This lead SNP is also close to the growth hormone receptor, GHR [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…per lactation, peak yield and persistency are considered as among the economically most important production traits in dairy cows (Dekkers, Ten Hag, & Weersink, 1998;Do et al, 2017;Tekerli, Akinci, Dogan, & Akcan, 2000). There is a considerable variation between animals in terms of the shape of the lactation curve, which can be attributed to factors such as genetic background, parity, diet, health status and other environmental factors (Atashi, Zamiri, & Dadpasand, 2013;Hostens, Ehrlich, Van Ranst, & Opsomer, 2012;Rekaya, Carabano, & Toro, 2000;Tekerli et al, 2000).…”
mentioning
confidence: 99%
“…It enhances the mammary gland's defense system during mastitis induced by Escherichia coli infection in goats (Zhu et al, 2007). A study performed on Canadian Holstein cattle on the enrichment of lactation persistency resulted in the identification of the cytochrome b5 reductase 3 (CYB5R3 ) gene (Do et al, 2017). Interestingly, in our research, the CYB5R3 gene showed a high co-expression with the GSN gene (Table S4 and Table S7).…”
Section: Genes Co-expressed With Degsmentioning
confidence: 64%